Environmental Protection Governance In Indonesia: A Siyāsah Tanfīdziyyah Analysis Of Regional Policy Implementation - Try Sutrisno; Zuhraini; Ahmad Fauzi Furqon (JURNAL ILMU SYARIAH, 2026)
Environmental sustainability is crucial for human life and must be protected from pollution and environmental degradation caused by development, industrial activities, and community activities. This study aims to analyze the implementation of Article 434 of South Sumatra Provincial Regulation Number 4 of 2024 on Environmental Protection and Management from social and administrative perspectives at the Environmental Agency of Ogan Komering Ulu Regency. Using a field research approach, data were collected through interviews, observations, and documentation involving five agency employees. The results indicate that environmental oversight has been carried out through direct and indirect monitoring, evaluation of reports, and follow-up on violations, although several technical and administrative obstacles remain. From a social and administrative perspective, this implementation reflects the principles of trust, justice, and general welfare (maslahah), demonstrating the government's responsibility to maintain environmental sustainability. Keywords: Social and Administrative Supervision; Environmental Protection and Management; Regulation